Exploring and extending the synergy concept – a study of three acquisitions. Issue 13 (6th April 2021) - Holtström, Johan; Anderson, Helén
Abstract : Purpose: This study aims to contribute with an extended framework on synergy realisation in acquisitions. The study conceptualises synergy realisation after acquisitions, in interaction with other companies in a business network and that synergy can be the result of both intended and not intended actions. Design/methodology/approach: The study is based on a company involved in acquisitions, being both the acquirer and the acquired. The data for analysis were collected through semi-structured interviews with managers involved in the described acquisition processes. The semi-structured interviews were guided by overarching themes to cover relevant areas of the described acquisitions. Findings: This study develops a framework in which synergy is used as a concept in business networks. The framework offers a more dynamic perspective on acquisition processes and extends the view of acquisition performance beyond more financial and company internal aspects of acquisition processes. Further, the findings show that related companies such as customers and suppliers, play important roles in synergy realisation. Practical implications: From a managerial perspective, the study shows the importance of understanding the underlying forces of integration processes. Originality/value: The concept of synergy used in this study not only includes the companies integrated in an acquisition but also their business networks. Including the integrated companies and their business networks provides a more dynamic perspective from which to plan and realise synergy.